Applications for a neutron-emitting plasma focus - Freeman, B.L.; Fowler, C.M.; McDaniel, F.D. (IEEE Conference Record - Abstracts. 1996 IEEE International Conference on Plasma Science, 1996)
Summary form only given. The plasma focus device produces the smallest source size, highest instantaneous flux, pulsed neutron source of any fusion-reaction based system when it is operated in the high pressure mode. Specifically, the neutron emission region has been measured to be -1 cm long and /spl lsim/2 mm diameter. Neutron yields as high as /spl gsim/10/sup 12/ neutrons/pulse (n/p) have been produced from the D(D,n)/sup 3/He reaction (DD). The scaling of such yields to their equivalent D(T,n)/sup 4/He neutron (DT) yields by a factor of 80 to 100 has been demonstrated. The pulse width of these neutron yields is /spl lsim/100 ns, from many measurements, Therefore, the plasma focus can produce DD neutron yields of /spl gsim/10/sup 12/ n/p and DT neutron yields of /spl sim/10/sup 14/ n/p without any extension of this machine's demonstrated operating range. At the upper end of these yields, the DT reaction provides instantaneous fluxes of /spl gsim/10/sup 21/ n/s, neutron densities of /spl lsim/10/sup 9/ n/cm/sup 2/ at 1 m from the source, and instantaneous flux densities of /spl lsim/10/sup 16/ n/cm/sup 2/-s. Given these characteristics as a starting point, such a neutron source can be utilized for several applications within the presently recognized operating bounds of the plasma focus.